Microbialites at Gusev Crater, Mars - Bianciardi, Giorgio (2015)
The Mars Exploration Rover Spirit investigated plains at Gusev crater, where sedimentary rocks are present. The Spirit rover’s Athena morphological investigation shows microstructures organized in intertwined filaments of microspherules: a texture we have also found on samples of terrestrial stromatolites and other microbialites. We performed a quantitative image analysis to compare 45 microbialites samplings with 50 rover’s ones (approximately 25,000/20,000 microstructures). Contours were extracted and morphometric indexes obtained: geometric and algorithmic complexities, entropy, tortuosity, minimum and maximum diameters. Terrestrial and Martian textures resulted multifractals, while terrestrial abiogenic minerals showed a simple fractal structure. Mean values and confidence intervals from the Martian images overlapped perfectly with those from terrestrial samples. The probability of this occurring by chance was less than 1/28 , p<0.004. Our work show the presumptive evidence of microbialites in the Martian outcroppings explored by “Spirit”, confirming our previous results concerning the Martian outcroppings explored by Opportunity at Meridiani Planum: unicellular life was widespread on the ancient Mars.